On the problem of synthesis of nano-optical elements - Goncharsky, A.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2008)
The paper deals with the mathematical modeling of synthesis of nano-optical elements. The accuracy of the computation and manufacturing of flat phase optical elements to form the images at optical wavelength is specified in terms of the Fresnel approximation. It is shown that the microrelief of a nano-optical element operating at optical wavelengths must be shaped to an accuracy of the order of 10 nm. Key words: mathematical modeling, synthesis of nano-optical elements, microrelief formation